The Mechanism of Traditional Chinese Medicine Based on Semi-Targeted Metabolomics to Improve IVF Outcomes in Senile Patients. (10th November 2021) - Ma, Ying-Jie; Yuan, Li-Hua; Xiao, Ji-Mei; Jiang, Hua-Ying; Sa, Yuan-Hong; Sun, Hong-Qi; Song, Jing-Yan; Sun, Zhen-Gao
Abstract : Objective . To identify the biological function and metabolic pathway of differential metabolites in follicular fluid of senile patients with kidney qi deficiency undergoing in vitro fertilization-embryo transfer (IVF-ET) and observe the effect of kidney-invigorating herbs on IVF outcomes in senile patients. Methods . A total of 95 women undergoing IVF treatment were recruited and divided into three groups, including 34 cases in the treatment group (the senile patients with kidney qi deficiency after the intervention of Chinese medicine), 31 cases in the experiment group (the senile patients with kidney qi deficiency of no intervention of Chinese medicine), and 30 cases in the control group (young women with infertility due to male factor). The three groups of women were treated with long protocol ovarian hyperstimulation; the treatment group was given Qi-Zi-Yu-Si decoction on the day of HCG downregulation. Their IVF clinical outcomes were observed. The metabolites changes of kidney qi deficiency syndrome were analyzed in follicular fluid metabolomics using liquid chromatography-mass spectrometry (UPLC-MS/MS). Results . The syndrome score of kidney qi deficiency syndrome in the treatment group was significantly improved after treatment (P < 0.01 ). Compared with the experiment group, the available embryo rate and implantation rate were increased, and the difference was statistically significant (P < 0.05 ). Progesterone, indoleacrylic acid, 2-propenyl 1-(1-propenylsulfinyl) propyl disulfide, N-acetyltryptophan, decanoylcarnitine, 20a-dihydroprogesterone, testosterone acetate, eicosatrienoic acid, 1H-indole-3-carboxaldehyde, choline, phosphorylcholine, and tryptophan were downregulated in the treatment group. Through pathway analysis, glycerophospholipid metabolism and steroid hormone biosynthesis were regulated in senile patients with kidney qi deficiency after Qi-Zi-Yu-Si decoction intervention. Conclusion . Qi-Zi-Yu-Si decoction can effectively improve the IVF outcome and clinical symptoms of senile patients. Follicular fluid metabolites were significantly changed in senile infertile women with kidney qi deficiency, and the mechanism by which kidney-invigorating herbs improve IVF treatment outcomes may be related to glycerophospholipid metabolism and steroid hormone biosynthesis. This study was registered in the Chinese Clinical Trials Registry Platform (ChiCTR1800014422 ).